2000
DOI: 10.1002/14651858.cd001481
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to improve the management of diabetes mellitus in primary care, outpatient and community settings

Abstract: Interventions to improve the management of diabetes mellitus in primary care, outpatient and community settings (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
398
1
18

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 414 publications
(424 citation statements)
references
References 71 publications
7
398
1
18
Order By: Relevance
“…A meta-analysis was performed in eight reviews [9-11, 13, 15, 16, 18-20]. A total of six reviews exclusively used qualitative data synthesis [21][22][23][24][25][26][27] (ESM Table 11). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A meta-analysis was performed in eight reviews [9-11, 13, 15, 16, 18-20]. A total of six reviews exclusively used qualitative data synthesis [21][22][23][24][25][26][27] (ESM Table 11). …”
Section: Resultsmentioning
confidence: 99%
“…In eight reviews, experts in the field were contacted to identify additional publications [10,11,13,15,[18][19][20]25]. Reference tracking was performed in 11 reviews [10,11,13,15,16,[18][19][20][21][22]24]. Predefined contact of all authors was not reported in any review.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The effectiveness of the different interventions carried out by primary care professionals to improve the management of diabetic patients depends on the reduction of the high cardiovascular risk in these patients [10]. We have studied the incidence, prevalence, complications, and cardiovascular risk factors of known Type 2 diabetes in the Basque Country in northern Spain.…”
mentioning
confidence: 99%